2002
DOI: 10.1021/bi020058l
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Biological Role of Nitric Oxide Binding to Cytochrome c‘

Abstract: The binding of nitric oxide to ferric and ferrous Chromatium vinosum cytochrome c' was studied. The extinction coefficients for the ferric and ferrous nitric oxide complexes were measured. A binding model that included both a conformational change and dissociation of the dimer into subunits provided the best fit for the ferric cytochrome c' data. The NO (nitric oxide) binding affinity of the WT ferric form was found to be comparable to the affinities displayed by the ferric myoglobins and hemoglobins. Using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 20 publications
2
53
0
Order By: Relevance
“…A model in which Cyt cЈ serves to shuttle NO has been previously proposed (23). In this model, NO binds to reduced Cyt cЈ.…”
Section: Discussionmentioning
confidence: 99%
“…A model in which Cyt cЈ serves to shuttle NO has been previously proposed (23). In this model, NO binds to reduced Cyt cЈ.…”
Section: Discussionmentioning
confidence: 99%
“…The wild type RC strain was further shown to produce N 2 O when grown in the presence of NO, leading to the suggestion that RCCP is involved in reductase activity (8). Particularly since NO-reductase activity has not been demonstrated for purified RCCP or any other cytochrome cЈ, it is possible that cytochrome cЈ could be a transporter coupled to a NO reductase, as recently proposed for the species Chromatium vinosum (53) and Rhodobacter sphaeroides (54). In the context of a physiological NO binding role for AXCP, the overall picture is that the distal side controls the initial NO binding, whereas the proximal heme pocket controls the release of NO with the ability of trapping and gating NO despite its close proximity to solvent with a virtually unidirectional release of NO.…”
mentioning
confidence: 93%
“…Despite their ubiquity in bacteria, the biological role of cytochromes c¢ remains unclear. Although a role in electron transfer processes had been assumed for a long time [7], more recently it has been suggested that cytochromes c¢ are involved in protection against high levels of NO [8,9]. Scientific interest in cytochromes c¢ has increased further owing to the similarities in spectral properties and ligand binding properties between cytochrome c¢ from Alcaligenes xylosoxidans and sGC [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Most cytochromes c¢ are isolated as stable homodimers, although some occur as monomers or as a mixture of both [16]. Cytochrome c¢ from the purple photosynthetic bacterium Allochromatium vinosum (cyt-c¢) displays a unique dimer-to-monomer transition upon binding of NO, CO, CN -or small alkyl isocyanides [9,[17][18][19]. Like in many gas-sensing proteins [4,20], the selectivity in ligand binding arises from steric hindrance of the vacant coordination site [21].…”
Section: Introductionmentioning
confidence: 99%